The implementation of Mini Darul Niswah and its impact on women empowerment / Nor Shahira Md Nor - Md Nor, Nor Shahira (Academy of Contemporary Islamic Studies, 2018)
Mini Darul Niswah is one woman stop center which has been establishing in the Kelantan by the State Government. The purpose of this establishment is because to increase the economy among the Kelantan women. Kelantan shows among the highest percentage of poverty in Malaysia. The objective of this study is to know the implementations of Mini Darul Niswah and its Impacts on Women Empowerment. This study focused on the activities that have been done at the Mini Darul Niswah especially for Mini Darul Niswah Mengkebang and Chempaka. The interview has been done in order to complete this research and the researcher has interview 15 people which are the staff of Urusetia Pembangunan Wanita, Keluarga dan Kebajikan Kerajaan Negeri Kelantan, the management of Mini Darul Niswah itself, the students and the alumni of Mini Darul Niswah. The interview questions consist of two sections which are for Section A- Demographic and Section B- The Implementations of Mini Darul Niswah and Its impacts on Women Empowerment. From the results receive, the students and alumni gain a lot of knowledge and skills at the Mini Darul Niswah and it gives a lot of impact to the women in increasing their economic.